Trends in the incidence, mortality, and survival rate of cardiovascular disease in a Japanese community: the Hisayama study - Kubo, Michiaki; Kiyohara, Yutaka; Kato, Isao; Tanizaki, Yumihiro; Arima, Hisatomi; Tanaka, Keiichi; Nakamura, Hidetoshi; Okubo, Ken; Iida, Mitsuo (Stroke (1970), 2003)
The slowdown of a steeply declining trend in cardiovascular mortality has been reported in Japan, but precise reasons for this trend are uncertain. We established 3 study cohorts of Hisayama residents aged > or =40 years without a history of stroke or myocardial infarction in 1961 (1618 subjects, first cohort), 1974 (2038 subjects, second cohort), and 1988 (2637 subjects, third cohort). We followed up with each cohort for 12 years, comparing the incidence, mortality, and survival rate of cardiovascular disease. The age-adjusted incidence of cerebral infarction significantly declined by 37% for men and by 32% for women from the first to the second cohort. It continued to decline by 29% for men, but the decline decelerated for women in the third cohort. The incidence of cerebral hemorrhage steeply declined by 61% from the first to the second cohort in men only, while it was sustained for both sexes in the third cohort. Stroke mortality continuously declined as a result of these incidence changes and significant improvement of survival. In contrast, the incidence and mortality rate of coronary heart disease were unchanged except for the increasing incidence in the elderly. The prevalence of severe hypertension and current smoking significantly decreased, while that of glucose intolerance, hypercholesterolemia, and obesity greatly increased among the cohorts. Our data suggest that the decline in stroke incidence is slowing down and that the incidence of coronary heart disease has been increasing in the elderly in recent years. Insufficient control of hypertension and the increase in metabolic disorders may contribute to these trends.